(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2023)
The most devastating disease that affects ginger production and productivity in Southwestern Ethiopia and lowers qualitative and quantitative rhizome yields is ginger leaf spot, which is caused by the pathogen Phyllosticta zingiberi. In Tepi, Southwestern Ethiopia, during the main cropping seasons of 2020 and 2021, a field experiment was carried out to assess the efficacy of several fungicides in managing epidemics of ginger leaf spot disease. The fungicides evaluated were Ridomil Gold MZ 68 WG (Metalaxyl-M), Ethiozeb 80% WP (Mancozeb), Shega 50 WP (Copper oxychloride), and Matico (Metalaxyl 8% + Mancozeb 64% WP). While the plot without spray is used as control. The results of the experiment indicated that among the different fungicides tested four times spray of Matico (Metalaxyl 8% + Mancozeb 64% WP) starting from the appearance of the disease on the field within 15 days intervals produced the lowest leaf spot disease severity of 10.2% followed by foliar spray with Mancozeb (Ethiozeb 80% WP) 16.2% first at disease appearance and then 3 times at 15 days intervals. Similarly, the highest yield of 16.3 t ha-1 was also obtained by foliar from the plot foliar spray of Matico (Metalaxyl 8% + Mancozeb 64% WP) which is followed by spraying with Mancozeb (Ethiozeb 80% WP) with a yield of 12.56 t ha-1. Therefore four times foliar spray of Matico @ 2.5 kg ha-1 is highly effective against leaf spot disease of ginger in southwestern Ethiopia. Int. J. Agril. Res. Innov. Tech. 12(2): 134-137, December 2022